DEVELOPMENT OF A METHOD FOR CALCULATING SECONDARY SIGNS OF DISEASE BY ITS PRIMARY SYMPTOMS - Zharkova, A. V.; Nahornyi, V. V. (Radio Electronics, Computer Science, Control, 2019)
Context. The article describes тhe actual problem of raising the informativeness of diagnostic signs (symptoms) ensuring the introduction of computer technologies, for example, in medical practice, for the rapid formulation of a reliable diagnosis has been solved. Objective. The goal of the work is to develop a methodology for quantitative assessment of the dynamics of symptoms and the unification of the form of their presentation for the formalization on this basis of the process of diagnosis and prediction of the moment of exacerbation of the disease. Method. Modern methods of diagnosis based on a comparison of the current values of symptoms with their normative maximum permissible values. However, the norms are based on average statistical data, which can only relate to a specific patient with a certain degree of probability. This is the cause of errors in predicting for this individual the moment of exacerbation of his disease. In this regard, using the example of cardio disease to solve this problem, it was proposed for the first time to supplement the traditional method of diagnosis with the calculation of secondary informative signs (indicators). At the same time, the process of making a diagnosis in accordance with the rules of discriminant analysis consists in comparing indicators with a limited number of clusters describing consistently worsening disease pathology. Thus, it is possible to replace many combinations of the values analyzed at the diagnosis of symptoms with a finite series of clusters, which significantly increases the speed of diagnosis and is a necessary condition for the computerization of the diagnosis process itself. Results. The reviewed methodology was successfully tested to control the severity of three patients with coronary heart disease, allowing retrospectively predicting the actual calendar date of exacerbation of the disease, which in practice allows you to plan the optimal strategy for timely treatment of the disease. Conclusions. A methodology has been developed to increase the informativeness of the symptoms of the disease, formalizing the process of diagnosis and thereby ensuring the introduction of computer technology into medical practice in order to promptly determine for each patient the time of exacerbation of his disease and to establish a reliable diagnosis on this basis